Kewarganegaraan dan Sistem Pendidikan : Pengaruh Globalisasi Terhadap Kurikulum Kewarganegaraan di Sekolah Indonesia - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Salma Nabila; Mukhamad Diki Indarto; Tri Wulan Sari (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study investigates the impact of globalization on the citizenship curriculum in Indonesian schools. As globalization integrates and connects diverse cultures, it has significantly influenced educational systems, including how citizenship is taught. This research examines changes in the citizenship curriculum through document analysis and educator interviews, assessing how these changes affect students' understanding of national identity. The findings reveal that while globalization provides opportunities to broaden students' global perspectives, it also poses challenges in balancing global values with the preservation of national identity. The study recommends incorporating global elements into the curriculum while maintaining a strong emphasis on local context to develop well-rounded citizens with a robust sense of national identity. Keywords:, ,,